1984
DOI: 10.1080/00362178485380371
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic activities ofTrichophyton rubrumand the chemotaxis of polymorphonuclear leucocytes

Abstract: The enzymic activity of Trichophyton rubrum has been investigated in relation to the plasmadependent chemotaxis of polymorphonuclear leucocytes (PMNs). In Boyden-type experiments use of a cytoplasmic extract of T. rubrum (CETr) produces neutrophil ehemotactic factor (NCF) from plasma. CETr was shown to have activity for eight enzymes: heat treatment of CETr led to a partial loss of activity for seven enzymes and a significant reduction in the number of PMNs migrating. Addition of CETr to plasma and incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…As expected, all of the enzymes that we detected extracellularly belonged to the panel of T. rubrum enzymes which were previously described by the same method [8]. Furthermore, our findings demonstrate that the spectrum of enzymes released by ' T. rubrum is strongly dependent upon nutritional conditions used.…”
Section: Discussionsupporting
confidence: 84%
“…As expected, all of the enzymes that we detected extracellularly belonged to the panel of T. rubrum enzymes which were previously described by the same method [8]. Furthermore, our findings demonstrate that the spectrum of enzymes released by ' T. rubrum is strongly dependent upon nutritional conditions used.…”
Section: Discussionsupporting
confidence: 84%
“…Inflammation in dermatophyte infections is the result of any combination of events, including: complement activation and production of complement-derived chemotactic factors, keratinocyte production of interleukin-8 and leukotriene B4, neutrophil and monocyte/ macrophage migration and activation. [7][8][9] Lufenuron may have acted at any of these sites or by some other yet undefined mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…T. rubrum or T. mentagrophytes may evoke these inflammatory reactions by activating complements. Davies, Swan, and Dahl et aI., using T. rubrum, and Tagami et aI., using T. mentagrophytes, observed that the fungus activated the complement system, to produce chemotactic factors (40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%